THE LEARNING MANAGEMENT SYSTEM (LMS) ACCEPTANCE LEVEL IN LEARNING TEACHER PERFORMANCE (TAM APPROACH) - Tri Sulistiyani, Elisabeth; Nugroho, Widyo (Dinasti Publisher, 2022)
The purpose of the study was to determine the Acceptance Level of the Learning Management System (LMS) in Learning on Teacher Performance (TAM Approach). Teacher performance that is still low in mastering LMS can result in low student learning outcomes. The research method used is quantitative with the type of survey. The research instrument used a questionnaire. Data analysis used the t test and F test. The results showed that teacher readiness had a positive and significant effect on teacher performance during the Covid-19 pandemic (t count 8.950 greater than t table 1.971 in sample 221 and = 0.05. Perception of using the Technology Acceptance Model (TAM) has a positive and significant effect on teacher performance during the Covid-19 pandemic (t count 9.673 greater than t table 1.971). Teacher readiness and perceptions of using the Technology Acceptance Model (TAM) have a positive and significant impact on teacher performance during the Covid-19 pandemic (F count 65.538 greater than F table (2:218) of 3.04 at = 0.05. The conclusion of the study is that if you want to improve the performance of teachers during the Covid-19 pandemic at SMA Negeri Depok City, then factors such as teacher readiness and perceptions of use Technology Acceptance Model (TAM) needs to be improved simultaneously The implications of the study show the variable perception of the use of the Technology Acceptance Model (TAM) need to be implemented by the teacher.